Analisis Faktor Dominan Yang Bergaruh Terhadap Keberhasilan Berwirausaha Pada Sarjana Universitas Sahid Surakarta - Sulistyadi, Kohar; Sukamdani, Nugroho Budisatrio (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2014)
The aim of this research are: 1) to find some factors of the characteristics of entrepreneurs that the most dominant influence on entrepreneurial success of USS graduates and 2) to give recomendation as strongestcharacteristics of entrepreneurs USS graduates. This research approach use quantitative methods with quasi-experimental especially correlational research. The samples research consisted of USS graduates has become successful entrepreneur. The research sample were 70 graduates of the total population taken by purposive sampling technique. The Design questionnaire used to collecting data, and data analysis technique was Factor Analysis that include: 1) Correlation Indicator: Kaiser-Meyer Olkin (KMO), 2) Extraction Factor: Principal Components Analysis, and 3) Factor Rotation: Varimax Method. The results of this study are as follows: 1) some factors of the characteristics of entrepreneurs that influence on  entrepreneurial success of USS graduates, namely: (1) have a clear vision and goals, (2) self-confidence, (3) optimism, (4) independent, (5) creative and innovative, (6) ambitious and energetic, (7) responsible, (8) originality, (9) future-oriented, (10) task-oriented and results, (11) has the soul of a leader, (12) dare to take risks, (13) honest, (14) jaunty and communicate, and (15) good at taking advantage of opportunities, 2) some factors of the characteristics of entrepreneurs that the most dominant influence on entrepreneurial success of USS graduates are: (1) have a clear vision, Mision and goals, (2) self-confidence and (3) has the soul of a leader.Keywords:     Characteristics of Entrepreneurs, Principal Component Analysis.